Rodríguez Bravo, M. F. (Coord.), Alcalá Ibáñez, M. L., Miguel Pérez, V., Camacho Prats, A., Galicia Mangas, F. J., Montero Alcaide, A. y Tébar Cuesta, F. (2022). Marco para el buen desempeño de la inspección educativa. Madrid, USIE, 148 pp. - Jesús Ocaña-Morena (Universidad de Navarra, 2023)
Book Review